Bartonella quintana Endocarditis of the Tricuspid and Mitral Valves - Alozie, A.; Yerebakan, C.; Westphal, B.; Podbielski, A. (The Thoracic and Cardiovascular Surgeon, 2012)
Bartonella quintana is a gram-negative microorganism that can lead to culture-negative infective endocarditis (IE) in immunocompromised patients. Here, we present an exceptionally rare case of a 70-year-old male with Bartonella quintana-associated IE primarily limited to the tricuspid valve that spread to the mitral valve after tricuspid valve replacement. This was then complicated by infective spondylodiscitis of the thoracic vertebrae, ultimately resulting in death due to cardiac arrest.
Keywords: infective endocarditis; Bartonella quintana; tricuspid valve